Applications - Abe, Jair Minoro [UNESP]; Akama, Seiki; Nakamatsu, Kazumi; Abe, JM; Akama, S; Nakamatsu, K (Springer, 2015)
This chapter discusses applications of annotated logics for various areas. After reviewing paraconsistent logic programming and generalized annotated logic programming, we survey promising applications to knowledge representation, neural computing, automation and robotics.